Detection of 2-photon photosensitized singlet oxygen in hollow-core photonic crystal fibres - Adan Bermudez, Sergio (The University of Edinburgh, 2022)
Photosensitized production of singlet oxygen is used in the treatment of cancer by photodynamic therapy (PDT), in which a photosensitizer is administered and excited locally in the tumour tissue, generating singlet oxygen to destroy, selectively, malignant cells. The use of two-photon excitation (2PE) in PDT has significant advantages in achieving enhanced spatial selectivity and greater depth of penetration through tissue. This is driving the development of new photosensitizers with high 2-photon cross-sections, but progress is inhibited by the difficulty of determining, in vitro, the efficiency of singlet oxygen production in response to TPE. In conventional experiments, the extremely high photon flux needed to achieve two-photon absorption is created by focusing a pulsed laser beam into a spot of about 1 μm in diameter. This minuscule (femtolitre) excitation volume makes the detection of two-photon-induced singlet oxygen generation extremely challenging. This thesis describes the development of an optofluidic system for the measurement of singlet oxygen quantum yields under 2PE, using hollow-core photonic crystal fibre (HC-PCF). HC-PCF allows the guidance of light in a well-defined fundamental mode within the hollow core, sustaining 2PE over long path lengths. When the fibre core is filled with photosensitizer solution, the intense light-matter interaction over a long path length enables ultra-sensitive detection of singlet oxygen. In the present work, the detection was achieved using a singlet oxygen-specific fluorescent probe, singlet oxygen sensor green (SOSG), employing a two-colour pump-probe methodology, with an 800-nm pump beam (2PE of photosensitizer) and a 488-nm probe beam (excitation of fluorescent probe) co-coupled into the hollow core of the fibre. Using this approach, it was possible to detect quantitatively singlet oxygen produced by 2PE of sub-micromolar concentrations ofphotosensitizer in an aqueous solution. The efficiency of singlet oxygen generation for a variety of PSs, including aluminium (III) phthalocyanine chloride tetrasulfonate chloride (AlPcS4), Meso-tetrakis (4-sulfonatophenyl) tetrasulfonate porphyrin (TPPS4), Protoporphyrin IX (PPIX), Zinc phthalocyanine tetrasulfonate (ZnPcS4), Chlorin E6 (CE6), Flavin Mononucleotide (FMN) and Hypericin (Hyp), was measured relative to a reference standard, Rose Bengal (RB). The parameter obtained directly from these measurements was the product of the cross-section for two-photon absorption (2PA) and the singlet oxygen quantum yield. To extract the value of the 1O2 quantum yield, the 2PA cross-section was measured in separate, cuvette-based experiments. 2PA cross-sections were determined by measuring the two-photon brightness (product of 2PA cross-section and fluorescence quantum yield) of the PS relative to a standard fluorescent dye. To extract the value of the 2PA cross-section, the fluorescence quantum yield was measured, under one-photon excitation. For many of the PSs, this was the first time that the 2PA cross-section had been determined in biologically relevant, aqueous conditions. In some cases, aggregation effects were seen, where the 2PA cross-section value depended on the concentration of the PS. Singlet oxygen quantum yields were also measured under one-photon excitation, in cuvette experiments, using SOSG, to provide reference values for comparison with those measured under 2PE in HC-PCF. These experiments also revealed the effects of aggregation on singlet oxygen quantum yields. The work presented in this thesis has demonstrated, for the first time, that the unique optofluidic properties of hollow-core photonic crystal fibre enable singlet oxygen quantum yields of two-photon-excited photosensitizers to be measured, under conditions relevant to clinical application, in aqueous solution and using low pulse-energy excitation.
Keywords: potodynamic therapy; PDT; two-photon excitation; 2PE; photonic crystal fibres